Strategi Pengembangan Pariwista untuk Pemberdayaan Ekonomi Masyarakat Pesisir dalam Perspektif Ekonomi Islam: Studi pada Kecamatan Pesisir Tengah Kebupaten Pesisir Barat - Andre Giovano; Dimas Pratomo; Diah Mukhminatul Hasimi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to analyze the influence of the Tourism Development Strategy on the Economic Empowerment of Coastal Communities in Pesisir Tengah District, Pesisir Barat Regency, viewed through the perspective of Islamic Economics. Coastal tourism holds significant potential as a leading sector that can enhance the welfare of the local community. This study employed a quantitative approach using a survey method, involving 100 respondents from the coastal community in Pesisir Tengah District. The data were analyzed using Simple Linear Regression Analysis and Hypothesis Testing (T-test). The results indicate that the community's perception of both the Tourism Development Strategy and the Economic Empowerment of Coastal Communities variables is in the very high category (above 90%). Statistically, the hypothesis test proves that the Tourism Development Strategy has a positive and significant influence on the Economic Empowerment of Coastal Communities. This is evidenced by the tcount value of 2.482, which is greater than ttable (1.660), with a significance value of 0.015 which is less than 0.05. The implemented strategy, such as capacity building and access to capital, is proven effective in empowering the local economy. Furthermore, this tourism development is assessed as being in alignment with the principles of Islamic Economics, emphasizing maslahah (public interest), justice, and balance in social, economic, and environmental aspects, thereby creating comprehensive and sustainable welfare.